KONTROVERSI PENGGANTIAN CALON WAKIL WALI KOTA DALAM PEMILIHAN KEPALA DAERAH KOTA BAUBAU 2024 - Farid Yusud Nur Achmad Achmad (Journal Publicuho, 2025)
The 2024 Baubau City Regional Election was marked by controversy surrounding the replacement of the vice mayoral candidate by the Baubau City Election Commission (KPU). This replacement process sparked public debates, especially regarding the authenticity of the documents used for replacing the candidate, including a false certificate related to the candidate's alleged mental health condition. This study aims to analyze the causes, processes, and impacts of this controversy on public trust in the KPU and the local election process. The study adopts a qualitative approach, collecting data through in-depth interviews, document analysis, and observation. The findings reveal that the candidate replacement process, without adequate verification, has the potential to undermine the integrity of the election. The impact includes a decline in public trust in the local democratic process. This study recommends the need for stricter procedures and transparency in every stage of the election, particularly in controversial candidate replacements.